Crafting Connections: Unpacking Generational Linkages of Craftsmanship, and Memorialising Cultural Traditions - Petersen, Leila (School of Architecture, Planning and Geomatics, 2023)
The focus of this thesis is the notion of craft as both a product and a practice. The research is approached with an understanding that in the context of a post-apartheid South Africa, the long-standing tradition of craft and craftsmanship stands as an important expression of the desired communal nature of South African society. Here, the term ‘craft' is used to refer to traditional hand-methods of making in practices of beading, weaving, woodwork, crochet, knitting, and sewing. Using a personal connection to craft as a starting point, the research is extended to unpack overarching ideas of craft as a generational link that is embedded in memory and culture, the value and holistic benefits of craft, and the potential for traditional crafts to be reintegrated into contemporary micro-enterprises. Presently, we see the emergence of craft in both formal and informal sectors of society as there exists a newfound appreciation for traditional cultural values which has sparked the resurgence of craft sale to the public. A substantial portion of the production of crafts in the informal urban craft industry takes place in townships. As such, the selected site of inquiry is the eastern portion of Philippi, in the Western Cape of Cape Town, South Africa. This thesis proposes that through the design of a building or series of spaces that accommodate for the making of crafts and exchange of craft knowledge, craft networks can be established and embedded within communities, promoting creativity and craftsmanship. As an entry way into the economy for under-resourced communities, craft and craft production can facilitate that even the most economically disadvantaged sectors of society can have craftspeople who are able to develop their skills through learning from each other. Issues and constraints on site include navigating scales from the large-scale industrial buildings to the small-scale housing and informal settlements. By drawing from the existing busyness on site, this project attempts to organise busy nodes of activity while still accommodating for a degree of informality to seamlessly co-exist alongside private and semiprivate public space. In reflecting on the final design and full body of work, it can be noted that indeed, the principle of organising informality is one that is contradictory, but the attempt to do so is not all meaningless. There is value in taking lessons from existing craft practices within the Philippi community and seeing how, and in which ways, craft sectors can be bolstered and developed for the benefit on the community. It can be said firmly that through the use of craft and craftsmanship, there is huge potentials for communities of makers and entrepreneurs to racially desegregate the distribution of occupations by relying on existing skills that are embedded in both memory and culture.